If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = x + -18 Reorder the terms: 3(-2 + x) = x + -18 (-2 * 3 + x * 3) = x + -18 (-6 + 3x) = x + -18 Reorder the terms: -6 + 3x = -18 + x Solving -6 + 3x = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 3x + -1x = -18 + x + -1x Combine like terms: 3x + -1x = 2x -6 + 2x = -18 + x + -1x Combine like terms: x + -1x = 0 -6 + 2x = -18 + 0 -6 + 2x = -18 Add '6' to each side of the equation. -6 + 6 + 2x = -18 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = -18 + 6 2x = -18 + 6 Combine like terms: -18 + 6 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| d+4d+5d=180 | | ln(x-4)-ln(x-5)=4 | | 10y+44+48-2y=156 | | -9y+3y-7=6+4y-13 | | V/23=11 | | 5n-8=2 | | 3(40)-15=x+25 | | 4+m=3m | | n/10+6=12 | | 3x-2=24x-23 | | n/10+6=14 | | X^2-19x+14=-70 | | 3(x+5)=2x+1 | | x=-5(1) | | 8-4x=28-2x | | 12cos(3x)=0 | | 7x+13-9x=20-18x+16x-7 | | -14-5x=13-6x | | 9x^2-21x+7=-3 | | 7+13n= | | 8-4x=28-4x | | y-6x=13x | | x^2=364 | | X^2-17x+44=-4x+2 | | 8x+10y=106 | | 1.2=x-2.76 | | 2x+15=3x+10 | | 7+8n= | | 0.10x+0.35(50)=26.5 | | 7-8n= | | X+(3X-8)=360 | | 2m+8=8(1+7M) |